Gerbils from populations located in low vegetation habitats emerge later than those from more densely vegetated habitats. Issue 6 (2nd November 2022) - Menezes, Jorge F.S.; Tiano, Inbal; Kotler, Burt P.
Abstract : How personality changes across different populations is still a poorly studied topic. We compared Allenby's gerbils ( Gerbillus andersoni allenbyi ) from three different populations in the Negev Desert regarding their latency to emerge from a shelter and explore new environments. These three localities represented a gradient of vegetation cover (Kmehin < Shivta Dunes < Shivta Flats) and thus of predation risk. Furthermore, two populations were in sand dunes (Kmehin and Shivta Dunes) and the other in sandy flats. We expected individuals from the same population to show the similar latency, and to differ from that of the other localities. We collected five individuals from Kmehin, 10 in Shivta Dunes, and 12 in Shivta Flats. We tested their latency 3 times in two different contexts (a lit chamber, and the same chamber darked). We found latency to be repeatable in both contexts. Using a generalized linear mixed model, we found support for an interaction between context and site and sex and site. Kmehin individuals had much longer latency in the light than all other combinations, and males had much longer latency in the first period. This supports the hypothesis that different locations can have consistent population phenotypes. We discuss how this effect may be caused by different quantities of predators or different numbers of bold individuals within each population.